Water fragmentation by Liq+ and Cq+ projectiles with MeV energies. (July 2015) - Wolff, W; Schuch, R; Cariatore, D; Otranto, S; Fregenal, D; Bernardi, G; Suárez, S
Synopsis: We report on fragment distributions from water targets by impact of Li q+ and C q+ projectiles with MeV energies. We identify fragment species as function of emission energy by using an electrostatic spectrometer and as function of velocity by a time of flight mass spectrometer (pulsing the beam at the injector of the Pelletron accelerator). An improved Coulomb explosion model married to CTMC simulations allows us to calculate the energy of each fragment for different fragmentation channels.